Leszek Mazepa – badacz kultury muzycznej Lwowa i Galicji - Mazepa, Тeresa (Musica Galiciana. Kultura muzyczna Galicji w kontekście stosunków polsko-ukraińskich, 2025)
The article deals with a well-known musicologist, researcher of the musical culture of Lviv and Galicia, cultural and public figure, long-time academic at the Mykola Lysenko Lviv National Music Academy and the Faculty of Music of the Rzeszow University Leszek Mazepa. The article analyses his biography, describes the process of formation of his worldview system and a set of scientific positions, their implementation in scientific, cultural and public activities. On the basis of the analysis of the most innovative and significant works, the principles of his scientific activity are systematised and generalised. The author outlines the range of scientific interests of L. Mazepa, the peculiarities of his style of scientific activity, the specifics of argumentation, discussion and polemics regarding established pseudo-scientific positions. Consideration of the methodological foundations, arguments and beliefs of the scientist in the field of comprehensive analysis of multicultural sources of musical history of the region creates the basis for assessing the significance of his achievements and further research in each of the areas initiated by L. Mazepa.